Efektivitas Health Edukasi terhadap Tingkat Stres pada Masyarakat Berbasis Dampak Pandemi COVID-19: The Effectiveness of Health Education on Stress Levels in Society Based on the Impact of the Covid-19 Pandemic - Ahmil, Ahmil; Hasnidar, Hasnidar; Sulfian, Wahyu (Jurnal Surya Medika (JSM), 2022)
The outbreak of the coronavirus disease 19 was first discovered in Wuhan, China, and spread to all corners of the world. Almost all countries reported finding cases. The ease with which the COVID-19 virus spreads and the high reported death rate caused by the COVID-19 virus has disrupted all lifelines, including the economic, social, and educational sectors, making people feel confused, anxious, stressed, and even frustrated. The purpose of this study was to analyze the effectiveness of health education on the level of stress in the community based on the impact of the COVID-19 pandemic in the Kawatuna sub-district, Mantikulore sub-district. This research is quantitative, with the research design being pre-experiment with one group pre-test and post-test design. The number of samples in this study was 130 respondents. Sampling using a purposive sampling technique. The statistical test used is the Wilcoxon test. The research results obtained are 0.000 ≤ 0.05, which means that health education affects stress levels in the community based on the impact of the COVID-19 pandemic in Kawatuna Village, Mantikulore District. This indicates that providing health education to people experiencing stress due to COVID-19 effectively reduces and even eliminates the stress they feel tense.